2018
DOI: 10.1002/adfm.201804629
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Micro/Nanofluidic Ion Transport Channels for Organic Cathodes in High‐Rate and Ultrastable Lithium/Sodium‐Ion Batteries

Abstract: Conjugated carbonyl compounds are considered as ideal substitutes for traditional inorganic electrodes in lithium/sodium ion batteries (LIBs/SIBs) due to their excellent redox reversibility and structural tunability. Here, a flexible sandwich‐structured 3,4,9,10‐perylenetetracarboxylic dianhydride (PTCDA)/reduced graphene oxide (RGO)/carbon nanotube (CNT) (PTCDA/RGO/CNT) composite film with bioinspired micro/nanofluidic ion transport channels and interconnected porous conductive frameworks is designed and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…The LUMO, HOMO and E g of the prepared PTCDA‐based cathode materials analyzed with density functional tight theory (DFTB) method can therefore be utilized for a quantitative comparison . Thus far, many studies have focused on the smart design of electroactive monomers with controlled electronic structures (namely preparation of different monomers), while we demonstrate here the improved electronic conductivity of prepared polymeric cathodes and electronic structure of PTCDA segments via simply engineering the length of interconnected alkyl chains.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The LUMO, HOMO and E g of the prepared PTCDA‐based cathode materials analyzed with density functional tight theory (DFTB) method can therefore be utilized for a quantitative comparison . Thus far, many studies have focused on the smart design of electroactive monomers with controlled electronic structures (namely preparation of different monomers), while we demonstrate here the improved electronic conductivity of prepared polymeric cathodes and electronic structure of PTCDA segments via simply engineering the length of interconnected alkyl chains.…”
Section: Resultsmentioning
confidence: 96%
“…3) Understanding of the influences of macromolecular structure modifications on the redox kinetics. Previous works are mainly focused on designing new monomer molecules for enhancing performance of the polymer cathode . Much less attention has been put on the studies of their redox kinetics which have major influences on the rate performance and stability …”
Section: Introductionmentioning
confidence: 99%
“…The relationships between the linear fittings of Z' and the square root in low frequency (ω -0.5 ) are shown in Figure 4e, the slope of which represents the Warburg factor to determine the Li + diffusion transportation. 60 It can be observed that the slopes of Li-S batteries with PI, PI/PA and PI/PA-PVA separators are 12.2, 63.1 and 43.4, respectively, which are much less than that for assembling Celgard separator (80.1), further confirming that the PI nanofiber-based separators show the better Li + transportation in the Li-S battery. The galvanostatic discharge-charge profiles of Li-S batteries assembled with PI, PI/PA-PVA and Celgard separators at 0.1 C are displayed in Figure 4f.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 75%
“…[ 16 ] For this purpose, a wide catalog of materials are under research, such as conducting polymers, organosulfur compounds, organic radical compounds, carbonyl compounds (PTCDA and disodium rhodizonate). [ 18,80–82 ] These latter, carbonyl compounds, are the most studied family of organic electrodes in the last years, but they are still concerns that must be resolved. The main drawbacks of these systems are the dissolution of the cathode in the electrolyte that leads to rapid capacity fade, their low electronic conductivity that causes poor rate performance, and the increase of working potentials and tap density of the electrodes that would lead to high energy density cathodes.…”
Section: Sodium Ion Batteries: Retrospective and Advancesmentioning
confidence: 99%